Conceptions of Intrafamily Violence in the Educational Sector - Rachel Faria Brino; Mayra Aparecida de Oliveira Souza (Universidade Federal do Rio Grande do Sul, 2016)
The objective of this study was to investigate the conceptions of intrafamily violence among professionals and students of the education sector. We used an adaptation of the questionnaire Beliefs about Domestic Violence. The study included 58 participants. The quantitative analysis yielded means and the total percentages of appropriate and inappropriate responses of each group regarding all items of the instrument. Statistically significant differences in these items were also observed. Data showed statistically significant differences in 6 items and in the total score of each group. Students had more adequate conceptions than the professionals. Lastly, we highlight the need to implement continuous courses for professional updating.